Seabiscuit - Kennedy, Kathleen, 1954-; Marshall, Frank; Ross, Gary, 1956-; Sindell, Jane; Maguire, Tobey, 1975-; Bridges, Jeff, 1949-; Cooper, Chris, 1951-; Banks, Elizabeth, 1974-; Stevens, Gary, 1963-; Macy, William H., 1950-; DuCoeur, Kingston; Jones, Eddie; et al. (Universal City, CA : Universal, 2003)
Based on a true story. A half-blind ex-prizefighter and mustang breaker team up with a millionaire and his rough-hewn, undersized horse, Seabiscuit. The men bring Seabiscuit to incredible heights, helping to turn a long shot into a legend. Eventually, Seabiscuit earns Horse of the Year honors in 1938.
Title from container.
Based on the book by Laura Hillenbrand.
Special features: feature commentary with director Gary Ross and filmmaker Steven Soderbergh; bringing the legend to life: "The making of Seabiscuit"; anatomy of a movie moment; Seabiscuit: racing through history; photo finish: Jeff Bridges' on the set photographs; cast and filmmakers' biographies & film highlights; production notes.
Director of photography, John Schwartzman ; narrator, David McCullogh ; editor, William Goldenberg ; music, Randy Newman ; costume designer, Judianna Makovsky ; production designer, Jeannine Oppewall.
Tobey Maguire, Jeff Bridges, Chris Cooper, Elizabeth Banks, Gary Stevens, William H. Macy, Kingston DuCoeur, Eddie Jones.
MPAA rating: PG-13; for some sexual situations and violent sports-related images.
Keywords: Seabiscuit -- (Race horse), -- 1933-1947; Horse racing; Horse trainers; Feature films; Action and adventure films